Exploring the Environmental in South African Educational History - Chisholm, Linda (Encounters in Theory and History of Education / Rencontres en Théorie et Histoire de l'Éducation / Encuentros en Teoría e Historia de la Educación)

(untitled) (Faculty of Education, Queen's University, 2024)
This article takes a small part of South Africa’s oppositional history – the educational initiatives of social actors in exile – to show that ideas about environmental education were present in exile as much as in South Africa’s internal anti-apartheid movement. It builds on a South African historiography that problematises universalising notions of ‘development’ drawn from colonial modernisation discourses and tied to Western models of development. It focuses on the inclusion of Development Studies and environmental education in the curriculum of the exiled African National Congress’s (ANC’s) Solomon Mahlangu Freedom College (SOMAFCO) in the 1970s. Drawing on primary sources in the University of Fort Hare’s Liberation Movement Archives, the article argues that while the curriculum was part of a wider developmentalist discourse emerging in the post-WWII era; it aimed - unlike the apartheid curriculum which sought to construct and underline difference - to counter colonial racist discourses, and included environmental education in the curriculum at the suggestion of UNESCO. It could be seen as an early form of “decolonial” education. This case study is significant for deepening understanding of the history of environmental education in the global South.